Facilitating the development of clinical reasoning skills amongst undergraduate student nurses through action research - van Wyngaarden, A.; Leech, R.; Coetzee, I. (South African Journal of Higher Education, 2026)
Student-centered teaching and learning practices encourage critical thinking and clinical reasoning skills in nursing education, but these practices are challenging for nurse educators. This study followed an action research approach, which involved collective, self-reflective inquiry by the participating nurse educators to identify educational practices that will foster the development of clinical reasoning skills among undergraduate student nurses. This paper describes the action research applied, outlining the implementation and outcomes which led to a co-constructed action plan. Four challenges: teaching, learning, and assessment; the clinical learning environment; continuous professional development and support; as well as the selection of nurse educators and students was addressed. This reflective process contributed to nurse educators evaluating their own pedagogy and adapting their teaching and learning practices to foster clinical reasoning skills among nursing students.